Monitoring of trace metals, biochemical composition and growth of Axillary seabream (Pagellus acarne Risso, 1827) in offshore Copper alloy net cage - YIGIT, M.; CELIKKOL, B.; BULUT, M.; DWYER, R.; DECEW, J.; OZALP, B.; YILMAZ, S.; KAYA, H.; KIZILKAYA, B.; HISAR, O.; YILDIZ, H.; YIGIT, U.; et al. (Mediterranean Marine Science, 2016)
The study was conducted to assess trace metal contents, biochemical composition and growth performance of axillary seabream (Pagellus acarne Risso, 1827) cultured in a copper alloy mesh cage. A total of 400 axillary seabream (initial mean weight: 176.0±14.0 g), a new candidate species for the Mediterranean aquaculture, were stocked into a high-density polyethylene frame gravity cage and fed a commercial seabream diet for a period of 6 months. At the end of the feeding trial, fish reached a final weight of 264.8±16.8 g with a weight increase of 88.8 g and a feed conversion rate of 2.51. Overall, relative growth rate, specific growth rate and feed conversion ratio were satisfactory and comparable to the pelagic fishes such as gilthead seabream or European seabass, which are presently the main fish species for the Mediterranean aquaculture industry. Trace elements in fish grown in copper alloy net cages over a 6-month period showed satisfactory results, as the metal concentrations in fish tissues such as liver, skin, muscle and gills were below the reported upper limits for human consumption, indicating that copper alloy net is an acceptable and safe material for finfish cage aquaculture. Furthermore, from the growth performance data obtained in the present study, it can be concluded that axillary seabream showed potential for cage farming, and thus is a promising new candidate for the Mediterranean aquaculture industry.